Room-temperature processing of silver submicron fiber mesh for flexible electronics - Xiaopeng Bai (Nature Portfolio, 2018)
Electronics: Room temperature prepared silver nanofibers Silver fiber meshes prepared with draw spinning show outstanding optical, electrical and mechnical properties for flexible electronics. A team led by Hui Wu from Tsinghua University, China demonstrates a process to prepare submicron silver fiber mesh at room-temperature. The precursor mesh is cast via continuous draw spinning of the precursor solution and then converted to silver mesh after UV illumination. The mesh is patternable, transferrable and highly flexible due to the remaining polymer skeleton that is originally in the precursor and then survives the UV treatment. The whole process is compatible with industrial standards and produces ultra-fine silver mesh with high optical transparency (90%), low sheet resistance (9 Ohm sq−1) and excellent mechnical flexibility. They further demonstrate flexible electrochromic smart window and infrared stealth film to show the potential for industrial applications.